2018
DOI: 10.1166/jbn.2018.2568
|View full text |Cite
|
Sign up to set email alerts
|

Neural Stem Cells Alleviate Inflammation via Neutralization of IFN-γ Negative Effect in Ischemic Stroke Model

Abstract: Inflammatory response generated by ischemic stroke commonly affects functional or structural recovery. The aim of this study was to examine the IFN-γ caused inflammatory effects on NSCs in vitro and in vivo. We found that IFN-γ did not affect NSCs proliferation but increased the SOD2 level of inflammatory oxidative stress in NSCs culturing. High dose IFN-γ (500 ng) injection aggravated the level of inflammation in the cerebral ischemic model but did not alter the repairing functions of the NSCs in vivo. NSCs b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…Indeed, previous studies have shown that grafting of NSCs in prototypes of Alzheimer's disease, traumatic brain injury, hypoxic-ischemic injury, spinal cord injury and stroke resulted in reduced inflammation. [8,31,55,91,101,119,124] It has been shown that grafted NSCs ameliorate chronic CNS inflammation through several mechanisms. NSCs can reprogram the infiltrating inflammatory monocyte-derived cells into antiinflammatory myeloid cells via secretion of TGF-β2.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Indeed, previous studies have shown that grafting of NSCs in prototypes of Alzheimer's disease, traumatic brain injury, hypoxic-ischemic injury, spinal cord injury and stroke resulted in reduced inflammation. [8,31,55,91,101,119,124] It has been shown that grafted NSCs ameliorate chronic CNS inflammation through several mechanisms. NSCs can reprogram the infiltrating inflammatory monocyte-derived cells into antiinflammatory myeloid cells via secretion of TGF-β2.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Studies have shown that neural stem cells have a unique neuroprotective function that promotes functional recovery after acute SCI [10, 38]. In fact, previous studies have shown that neural stem cell transplantations can reduce inflammation in the prototype of traumatic brain injury, hypoxic ischemic injury, SCI, and stroke [39, 40]. However, it is difficult to assess the optimal NSC purification and transplantation times.…”
Section: Discussionmentioning
confidence: 99%
“…Stem cells have become the primary choice for transplantation therapy because of their "infinite" proliferation and multi-prospective differentiation potential. Moreover, stem cell transplantation therapy has been shown to promote the recovery of damaged tissues [52,53], including spinal cord, heart, brain, and liver. Previous researches have shown that cell proliferation can be found in subventricular zone in rat model disposed by the middle cerebral artery occlusion (MCAO), suggesting that endogenous recovery process is started after stroke [54][55][56][57].…”
Section: Exosomes Transplantation Therapy Directlymentioning
confidence: 99%
“…However, endogenous resilience may be limited due to hostile immune microenvironment over time [56,58]. In addition, the delayed inflammatory response to stroke leads to secondary neurological injury [52,58]. Insufficient endogenous stem cells after stroke can result in weak regeneration of nerve cells in the damaged area and slowdown in tissue function recovery.…”
Section: Exosomes Transplantation Therapy Directlymentioning
confidence: 99%